Strain-tunable electronic and magnetic properties of two-dimensional gallium nitride with vacancy defects - Yeoh, Keat Hoe; Chew, Khian Hooi; Yoon, Tiem Leong; Rusi, -; Ong, Duu Sheng (AIP Publishing, 2020)
Based on density functional theory, we have investigated the effects of in-plane biaxial strain on the electronic and magnetic properties of the two-dimensional GaN (2D GaN) with Ga- (VGa) or N-vacancy (VN). We considered two different levels of vacancy concentration, i.e., θ = 1 / 62 and θ = 1 / 34. While the pristine GaN 2D structures are intrinsically semiconducting, the 2D GaN with VGa defects under tensile/compressive biaxial strains is metallic, except at a high compressive strain of 6%. In addition, the 2D GaN exhibits a strain-tunable magnetic property by introducing the VGa defects, where the magnetic moment can be modulated by applying a biaxial strain on the material. A compressive strain larger than 2% tends to suppress the magnetic effect. A drastic reduction of the total magnetization from 2.21 μ B to 0.16 μ B is clearly visible for a lower VGa concentration of θ = 1 / 62. On the other hand, the 2D GaN with VN defects is nonmagnetic, and this behavior is not affected by the biaxial strain. © 2020 Author(s).